HUMAN SIALYLTRANSFERASES AND ITS INTERACTION WITH ANTICANCER PHYTOCHEMICALS - RAVNEET K GREWAL; ARUN SINGH PATHANIA; MOHIT CHAWLA (International Journal of Pharma and Bio Sciences, 2014)
Altered expression of sialyltransferases is well documented in cancer. Traditional anticancer drugs, mostly focus on inhibiting tumor cell growth or killing tumor cells directly or indirectly; however, there are only a few drugs that specifically inhibit metastasis of tumor cells. Curcumin and resveratrol are the phyto-chemicals with anticancer properties attribute their potential interference with molecular signaling related to cancer initiation and progression. In the present study, homology modeling is performed to generate the models for the human sialyltransferases involved in tumor metastasis i.e. GALα2,6-ST1, ST3GALSI3 and ST8A. The potential binding sites of these modeled proteins are identified, analyzed, and are subjected to docking studies with natural ligand i.e. CMP sialic acid and phytochemicals viz. curcumin and resveratrol. Our observations revealed that both resveratrol and curcumin are observed to have maximum interaction energy with sialyltransferases compared to their natural ligand suggesting that these phyto-chemicals may inhibit the targeted enzymes competitively. Cysteine is observed as a conserved residue of the L motif of enzymes under study, which is involved in interaction with the natural ligand. The docking studies of the natural ligand with ST8A also reinforce the role of ST8A enzyme in hypersialylation, which may have a possible role in cancer metastasis.